Structural coercion in the context of community engagement in global health research conducted in a low resource setting in Africa - Nyirenda, Deborah (BMC Med Ethics, 2020)
BACKGROUND: While community engagement is increasingly promoted in global health research to improve ethical research practice, it can sometimes coerce participation and thereby compromise ethical research. This paper seeks to discuss some of the ethical issues arising from community engagement in a low resource setting. METHODS: A qualitative study design focusing on the engagement activities of three biomedical research projects as ethnographic case studies was used to gain in-depth understanding of community engagement as experienced by multiple stakeholders in Malawi. Data was collected through participant observation, 43 In-depth interviews and 17 focus group discussions with community leaders, research staff, community members and research participants. Thematic analysis was used to analyse and interpret the findings. RESULTS: The results showed that structural coercion arose due to an interplay of factors pertaining to social-economic context, study design and power relations among research stakeholders. The involvement of community leaders, government stakeholders, and power inequalities among research stakeholders affected some participants’ ability to make autonomous decisions about research participation. These results have been presented under the themes of perception of research as development, research participants’ motivation to access individual benefits, the power of vernacular translations to influence research participation, and coercive power of leaders. CONCLUSION: The study identified ethical issues in community engagement practices pertaining to structural coercion. We conclude that community engagement alone did not address underlying structural inequalities to ensure adequate protection of communities. These results raise important questions on how to balance between engaging communities to improve research participation and ensure that informed consent is voluntarily given.